2017
DOI: 10.1016/j.ajo.2017.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Retinal Vasculitis and Predictors for Prognosis of Ischemic Retinal Vasculitis

Abstract: Retinal vasculitis is associated with an increased risk of vision loss, mainly secondary to macular ischemia, and has a higher risk of macular edema compared to eyes with no vasculitis. Ischemia involving ≥2 quadrants is a risk factor for new vessel formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Other diseases that can be associated with retinal vasculitis are Bechet's, Sarcoidosis, Multiple Sclerosis, Collagen-vascular disease, Sympathetic Ophthalmia, and others. 2,5,12,13 Retinal vasculitis can also be a part of posterior uveitis, where this disease is found in 6-15% of patients with posterior uveitis. Our study found that the history of TORCH infection was the most frequent systemic disease compare to other diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other diseases that can be associated with retinal vasculitis are Bechet's, Sarcoidosis, Multiple Sclerosis, Collagen-vascular disease, Sympathetic Ophthalmia, and others. 2,5,12,13 Retinal vasculitis can also be a part of posterior uveitis, where this disease is found in 6-15% of patients with posterior uveitis. Our study found that the history of TORCH infection was the most frequent systemic disease compare to other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study conducted by Sarief L, et al found that retinal vasculitis was found in 6-15% of uveitis patients. 5 The findings seen on funduscopic examination are usually from venous sheathing to vascular damage that affects the permeability of blood vessel walls. This results in leakage of blood into the retinal extracellular space and cystoid macular edema.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other middle-income countries, like India, a report showed that the incidence of infants > 1500 g treated for threshold ROP with cryotherapy was 15.3% [15]. And in Lithuania, 54% of the infants needing treatment for ROP were > 1500 g at birth [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Диагностически значимым также считается капиллярное просачивание в различных отделах сетчатки в сочетании с ликеджем в области ДЗН (так называемый «горячий» ДЗН), возникающим из расширенных капилляров вследствие первичной инфильтрации ДЗН или вторичных сосудистых изменений на фоне воспаления. При окклюзирующих формах нейроретиноваскулита возможны увеличение времени артериовенозного транзита, венозной перфузии, пульсирующий характер кровотока и выявление зон отсутствия капиллярной перфузии на периферии сетчатки [71].…”
Section: этиология и патогенез нейроретиноваскулита с вторичной окклюunclassified